2020
DOI: 10.1001/jamanetworkopen.2020.13201
|View full text |Cite
|
Sign up to set email alerts
|

Association ofMUC16Mutation With Response to Immune Checkpoint Inhibitors in Solid Tumors

Abstract: Key Points Question What is the association between MUC16 mutation and response to immune checkpoint inhibitors (ICIs) in solid tumors? Findings In this cohort study of 3 groups of patients, including The Cancer Genome Atlas cohort with 10 195 patients across 30 solid tumor types, 56 patients with non–small cell lung cancer, and 145 patients with melanoma, MUC16 mutation was associated with greater respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 39 publications
4
52
0
Order By: Relevance
“…35,36 A recent study indicated that the mutational frequency of MUC16 is 42.76% in lung adenocarcinoma, and 38.84% in lung squamous cell carcinoma, respectively. 37 Patients with MUC16 mutation have been found to have CD8A and PD-L1 positive is also higher in MUC16 mutated cases than in wild-type mutations. In addition, patients with MUC16 mutation receiving ICI treatment have also been associated with superior outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…35,36 A recent study indicated that the mutational frequency of MUC16 is 42.76% in lung adenocarcinoma, and 38.84% in lung squamous cell carcinoma, respectively. 37 Patients with MUC16 mutation have been found to have CD8A and PD-L1 positive is also higher in MUC16 mutated cases than in wild-type mutations. In addition, patients with MUC16 mutation receiving ICI treatment have also been associated with superior outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…This protein, thought to be the precursor of CA125 used as a biomarker for ovarian cancer, has been found to suppress the natural killer cell function which regulates tumor cell proliferation, metastasis and innate immune response 35,36 . A recent study indicated that the mutational frequency of MUC16 is 42.76% in lung adenocarcinoma, and 38.84% in lung squamous cell carcinoma, respectively 37 . Patients with MUC16 mutation have been found to have significantly elevated TMB compared to those without them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the decreased somatic mutation rate of MUC16 and the increased rate of TTN somatic mutations were significant features of CB. A recent study has shown that MUC16 mutations may be related to the efficacy of ICI therapy and to the improvement of prognosis-related genomic factors in solid tumors [ 34 ]. A possible mechanism for this is that MUC16 binds to the Siglec 9 receptor on NK cells, downregulating their cytotoxicity and thereby allowing tumor cells to escape immune surveillance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previously published pan-cancer analysis of 30 solid tumor types showed that patients with MUC16 mutations showed higher tumor mutation burden and neoantigen burden, indicating increased tumor immunogenicity, which can predict immune checkpoint inhibitor treatment response. The study included 397 cases of glioblastoma and 61 of these cases (15.37%) showed MUC16 mutations [14]. Therefore, we wondered whether the MUC16 mutation in G34-DHGs might also be associated with immune in ltration.…”
Section: Muc16 Mutation and Immune In Ltration Characteristics Of G34-dhgsmentioning
confidence: 99%